Role of Christian Religious Communicators in the Management of Menstrual Taboos: Revisiting the Historical Perspectives and Exploring its Modern Outlook - Xavier , Robin; Lakshmikantha , Nandini; Alex, Angel Treasa (International Journal of Psychosocial Rehabilitation, 2020)
The cultural and religious relationships of Christianity with Judaism has prompted Christian religious communicators to construct unfair laws for menstruants based on Judaic laws. Jesus, the role model of all Christian religious communicators, opposed this ruggedness vehemently. Irrespective of Jesus’ attempt, the patriarchy that prevailed in Christianity in the first century A.D, restricted women in religious practices due to attributed menstrual impurity. The stringent rules became trivial gradually as there is no report of a reformer or a definite period in history which claims this transformation. The present study explores the historical perspectives of menstrual taboos, the modern outlook of much progressive young Kerala Catholic Christian women, and the role of religious communicators in empowering women. Statistically significant results endorse Christianity as superior to any other religion in Kerala in their outlook towards menstruants and 93% advocates that religious practices should not be restricted for women during their menstruation.